Comparative Study of Nerve Grafting versus Distal Nerve Transfer for Treatment of Proximal Injuries of the Ulnar Nerve - Flores, Leandro Pretto (Journal of Reconstructive Microsurgery, 2015)
Background The prognosis for motor recovery associated with ulnar nerve injuries at a level proximal to the elbow is usually considered poor. Nerve transfers techniques were introduced as an alternative for the management of nerve lesions of the upper limb, aiming to improve the surgical results of those nerves for which direct reconstruction has not historically yielded good outcomes.Methods A retrospective chart review was conducted to compare the outcomes obtained using nerve grafting (20 cases) with those of distal nerve transfer (15 patients) for the treatment of proximal injuries of the ulnar nerve. Nerve transfer combined the suture of the anterior interosseous nerve to the motor branch of the ulnar nerve and the cooptation of its sensory branch to the third common digital nerve via an end-to-side suture.Results The Medical Research Council M3/M4 outcomes were observed significantly more often in the nerve transfer group (80 vs. 22%), and the mean values for handgrip strength were higher (31.3 ± 5.8 vs. 14.5 ± 7.2 kg). The groups were similar in attaining good sensory recovery (40 vs. 30%) and mean two-point-discrimination (grafting: 11 ± 2 mm; nerve transfer: 9 ± 1 mm). The mean value of the disabilities of arm, shoulder, and hand for the nerve transfer group (23.6 ± 6.7) was significantly lower than for grafting (34.2 ± 8.3).Conclusions Distal nerve transfer resulted in better motor and functional outcomes than nerve grafting. Both techniques resulted in similar sensory outcomes, and nerve grafting was demonstrated to be a better technique for managing the painful symptoms associated with the nerve injury.
Keywords: nerve transfer; grafting; regeneration; outcomes; ulnar nerve